The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1088/0953-8984/19/10/106210
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of giant magnetoresistance in Fe/Cr trilayers using layer potentials determined fromab initiomethods

Abstract: The ab initio full-potential linearized augmented plane-wave method explicitly designed for the slab geometry was employed to elucidate the physical origin of the layer potentials for the trilayers nFe/3Cr/nFe(001), where n is the number of Fe monolayers. The thickness of the transition-metal ferromagnet has been ranged from n = 1 up to n = 8 while the spacer thickness was fixed to 3 monolayers. The calculated potentials were inserted in the Fuchs-Sondheimer formalism in order to calculate the giant magnetores… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…While, MR p can directly reflect the spin-resolved interfacial scattering which dominates the electronic transport properties [57]. Then, a SV effect is reported that in metal layers, the interfacial scattering can either enhance or degrade MR p [58]. In our case, due to band match between the components of SV, T ↓ p , T ↑ ap and T ↓ ap at E F are almost zero which means the spin-resolved interfacial scattering can enhance MR p to almost 100%.…”
Section: Resultsmentioning
confidence: 99%
“…While, MR p can directly reflect the spin-resolved interfacial scattering which dominates the electronic transport properties [57]. Then, a SV effect is reported that in metal layers, the interfacial scattering can either enhance or degrade MR p [58]. In our case, due to band match between the components of SV, T ↓ p , T ↑ ap and T ↓ ap at E F are almost zero which means the spin-resolved interfacial scattering can enhance MR p to almost 100%.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the generalized gradient approximation provides more accurate results, Herper et al verified that this is due to a better geometry optimization [11]. Since the atomic positions are well known for our systems, LSDA is adequate [12]. The crystalline structure of our system is going to be considered as body-centered cubic (bcc), fitting with the known crystalline structures of both Fe and Cr bulk metals [13].…”
Section: Structure and Computational Detailsmentioning
confidence: 97%
“…For thin layers, it is reported that for 3ML, the stable Cr structure is an unstrained bcc [14]. Furthermore, we assume that the bcc structure is going to be held all along the system with the same lattice constant: α = 2.88Å, because it has been found that the difference between studying the system using both lattice constants for each respective metal slab, and using only one for both metals, is negligible [12]. For the above reasons, we are not going to allow any relaxation of the structure.…”
Section: Structure and Computational Detailsmentioning
confidence: 99%
“…The resistance of the single thin metallic layers was calculated lately by Paja and co-workers [2,3] for the binary and ternary alloys [4,5]. The transport properties for trilayers and multilayers were considered in [6].…”
Section: Introductionmentioning
confidence: 99%